UNVEILING THE ETHNOMATHEMATICS OF BANTUL'S NITIK BATIK: A CULTURAL AND MATHEMATICAL JOURNEY - Mufida, Naila Rahma; Azka, Raekha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
Ethnomathematics is the mathematics embedded in a culture or understood as a discipline used to understand how mathematics is adapted from a culture. The purpose of this study is to determine (1) What symmetry patterns are present in Nitik batik? and (2) What philosophical meanings are associated with the symmetry patterns in Nitik batik? These are specifically referenced for students, particularly in the context of teaching transformation geometry, by incorporating cultural elements, namely the Nitik batik motifs from Yogyakarta. Ethnomathematics, as a medium for teaching mathematics, also aims to introduce and preserve Indonesia's cultural heritage. This study employs a descriptive research method with a qualitative approach. The data used to answer the research questions were obtained from document studies, including books, journals, and internet sources. Data analysis was performed using qualitative data analysis techniques, which include three main steps: data reduction, data presentation, and drawing conclusions. The results of this study reveal that in the Nitik batik of Bantul Yogyakarta, the Jaya Kirana motif features geometric patterns of reflection and translation.